SOCIAL DYNAMICS OF GENDER VIEWS IN PHYSICAL EDUCATION IN THE SCHOOL ENVIRONMENT (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the social dynamics of gender within physical education activities, focusing on forms of resistance and identity negotiation in the school environment. Physical education not only plays a role in developing students’ physical fitness but also serves as a social space where gender values, roles, and power relations are reproduced and negotiated. This research employed a qualitative approach using semi-structured interviews with several teachers at UPT SPF SDI Pannampu 1 as participants. The findings reveal that physical education practices in schools are not entirely gender-neutral. Physical activities are still dominated by male students who are perceived as strong, active, and competitive, while female students tend to be directed toward activities considered soft or less challenging. These gender biases and stereotypes are reflected in the distribution of activities, social roles, and teaching practices of physical education teachers. However, the study also identified forms of resistance and identity negotiation, where some female students challenged traditional boundaries by participating in activities typically viewed as masculine. Teachers likewise began to develop critical awareness of the importance of creating an inclusive and equitable learning environment for all students. Therefore, physical education can be understood as a dynamic social arena where gender dominance and resistance coexist. The study highlights the need for implementing reflective and gender-sensitive pedagogical strategies to promote equality and inclusivity in school-based physical education.